HANDLING OF PAPUA ARMED CRIMINAL GROUPS: THE RESPONSIBILITY OF THE REPUBLIC OF INDONESIA - Pramono, Budi; Sunanto, Sunanto (Kertha Semaya : Journal Ilmu Hukum; Vol 11 No 10 (2023)DO - 10.24843/KS.2023.v11.i10.p16, 2023)
The purpose of this study is to analyze and identify the responsibility of the republik of Indonesia in handling the armed criminal groups of Papua. This research is normative legal research with a conceptual and statutory approach. Determination of terrorist status is not a solution to resolve conflicts because the determination of this status does not only have consequences for the qualifications of the crimes committed but also related to the model of law enforcement. The Papuan Armed Criminal Group is a serious problem which, if not handled properly, has the potential for the disintegration of the Indonesian nation, which in the end could disrupt the integrity of the Unitary State of the Republic of Indonesia. The Indonesian government must immediately take appropriate steps to resolve this because the problem is not only a domestic problem, but has also become the concern of the international community. The settlement can use a welfare approach by carrying out development in all fields, a military operation approach as well as a just law enforcement approach.